Comparison of Cut and Fill Volume Calculation Using Building Information Modeling (BIM) and Conventional Methods (Cut and Fill Project of KIT Batang, Block A Lots 9, 10, 11, 12, and 12A) - RAMADHONY, FERDY YOLA; WIDYANINGSIH, MAY KRISTINA; IKHWANUDIN, IKHWANUDIN; SUWANDI, PUTRI ANGGI PERMATA (International Journal of Sustainable Building, Infrastructure and Environment (IJOSBIE), 2026)
Abstract. Land preparation is a crucial initial stage in construction work to adjust the site’s topography to the planned elevation. One of the main activities in this phase is earthwork, specifically the cut and fill process. This study compares the conventional method and the Building Information Modeling (BIM) method in calculating earthwork volumes for the Cut Fill Project at KIT Batang, Block A Lots 9, 10, 11, 12, and 12A. The conventional method uses AutoCAD, Civil 3D, and Microsoft Excel with the Average End Area method, while the BIM method applies an integrated 3D digital model in Civil 3D through the Compute Materials and Volumes Dashboard commands. The results show that the conventional method produced excavation (cut) and embankment (fill) volumes of 5,715.65 m³ and 111,196.22 m³, respectively. Meanwhile, the BIM method generated 5,894.19 m³ (cut) and 112,093.61 m³ (fill) using Compute Materials, and 5,665.10 m³ (cut) and 112,038.57 m³ (fill) using Volumes Dashboard. The deviation of BIM results compared to the conventional method was less than 5%, with +3.12% and +0.81% for Compute Materials, and –0.88% and +0.76% for Volumes Dashboard. These small deviations indicate that the BIM method provides higher accuracy and efficiency, as it automatically calculates volumes based on an integrated digital surface model, reducing potential human error.Keywords: Cut and Fill, Earthwork, Conventional Method, Building Information Modeling (BIM), Civil 3D